Melaka Sustainability Outlook Diagnostic : Supporting Report 4 - Shaping a Compact, Efficient, and Harmonious Urban Form - Global Platform for Sustainable Cities; World Bank (World Bank, Washington, DC, 2019)
Melaka is a rapidly growing twenty-first century city in transition, increasing its population by forty percent in the last fifteen years in Malaysia. Rapid growth in population has fueled demand for new urban development, improved infrastructure and better services and facilities. Melaka has the vision to become a green city focused on addressing the important climate change and green growth agenda. Shaping efficiently its future urbanization is an essential enabling dimension of this vision for Melaka. Evidence linking efficient spatial planning and higher economic density with agglomeration economies, higher productivity and overall economic growth is well established. To achieve its economic goal of becoming a service economy, Melaka must create proximity and facilitate the flow of knowledge that fosters innovation. The spatial shape of Melaka must make it a center of productivity, human capital and greater access to markets. Adopting an integrated approach to land use and urban planning between geographical scales and economic sectors is critical to the orderly development of a sustainable city. This supporting report elaborates on Melaka’s land use and urban form.